2018
DOI: 10.12659/msm.913777
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Calcitonin Gene-Related Peptide Protects Against Focal Cerebral Ischemic Injury in Rats Through the Wnt/β-Catenin Pathway

Abstract: BackgroundIntranasal calcitonin gene-related peptide (CGRP) delivery offers a noninvasive method of bypassing the blood-brain barrier for the delivery of CGRP to the brain. Here, we first reported the therapeutic benefits of intranasal CGRP delivery in rats following middle cerebral artery occlusion (MCAO).Material/MethodsReal-time quantitative polymerase chain reaction (RT-qPCR) assay, enzyme-linked immunosorbent assay (ELISA), rat MCAO model, TTC (2, 3, 5-triphenyltetrazolium chloride) staining, hematoxylin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Low pH‐ and ischemia‐induced CGRP release from perivascular C‐fibers results in coronary and cerebrovascular vasodilation and restoration of circulation 10–12 . Treatment with CGRP improves and genetic ablation of CGRP worsens blood flow and outcomes after focal cerebral arterial occlusion in experimental animals 13–15 . Administration of CGRP has shown beneficial effects in peripheral and coronary artery disease 16–18 and ameliorated experimental cerebral and cardiac ischemia by preserving blood flow and the blood–brain barrier 15,19–21 .…”
Section: Introductionmentioning
confidence: 99%
“…Low pH‐ and ischemia‐induced CGRP release from perivascular C‐fibers results in coronary and cerebrovascular vasodilation and restoration of circulation 10–12 . Treatment with CGRP improves and genetic ablation of CGRP worsens blood flow and outcomes after focal cerebral arterial occlusion in experimental animals 13–15 . Administration of CGRP has shown beneficial effects in peripheral and coronary artery disease 16–18 and ameliorated experimental cerebral and cardiac ischemia by preserving blood flow and the blood–brain barrier 15,19–21 .…”
Section: Introductionmentioning
confidence: 99%
“…CGRP is one of the strongest vasoactive peptides found in vivo so far, which plays a role in relaxing and inhibiting vascular smooth muscle proliferation [ 6 , 7 ]. At the same time, CGRP can stagnate the cell cycle in G0/G1 phase and thus participate in the regulation of tumor growth [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The change of cell cycle is the driving force of tumor biological behavior [ 149 ], but whether it is unique in the role of cell cycle disorder in the occurrence of pancreatic cancer is still unknown. CGRP can induce G2/M phase arrest by regulating G2/M phase-related proteins [ 150 ]. Moreover, it is found that CGRP can arrest the cell cycle of pancreatic cancer stem cells in the G0/G1 stage [ 151 ].…”
Section: Cgrp and Tumor Stem Cellsmentioning
confidence: 99%